Digitally enabled disaster response: the emergence of social media as boundary objects in a flooding disaster. (5th October 2016) - Tim, Yenni; Pan, Shan L.; Ractham, Peter; Kaewkitipong, Laddawan
Abstract: In recent times, social media has been increasingly playing a critical role in response actions following natural catastrophes. From facilitating the recruitment of volunteers during an earthquake to supporting emotional recovery after a hurricane, social media has demonstrated its power in serving as an effective disaster response platform. Based on a case study of Thailand flooding in 2011 – one of the worst flooding disasters in more than 50 years that left the country severely impaired – this paper provides an in‐depth understanding on the emergent roles of social media in disaster response. Employing the perspective of boundary object, we shed light on how different boundary spanning competences of social media emerged in practice to facilitate cross‐boundary response actions during a disaster, with an aim to promote further research in this area. We conclude this paper with guidelines for response agencies and impacted communities to deploy social media for future disaster response.